Diel quenching of Southern Ocean phytoplankton fluorescence is related to iron limitation - Schallenberg, C; Strzepek, RF; Schuback, N; Clementson, LA; Boyd, PW; Trull, TW (Biogeosciences, 2020)
Evaluation of photosynthetic competency in time and space is critical forbetter estimates and models of oceanic primary productivity. This isespecially true for areas where the lack of iron (Fe) limits phytoplanktonproductivity, such as the Southern Ocean. Assessment of photosyntheticcompetency on large scales remains challenging, but phytoplanktonchlorophyll a fluorescence (ChlF) is a signal that holds promise in thisrespect as it is affected by, and consequently provides information about,the photosynthetic efficiency of the organism. A second process affectingthe ChlF signal is heat dissipation of absorbed light energy, referred to asnon-photochemical quenching (NPQ). NPQ is triggered when excess energy isabsorbed, i.e. when more light is absorbed than can be used directly forphotosynthetic carbon fixation. The effect of NPQ on the ChlF signalcomplicates its interpretation in terms of photosynthetic efficiency, andtherefore most approaches relating ChlF parameters to photosyntheticefficiency seek to minimize the influence of NPQ by working under conditionsof sub-saturating irradiance. Here, we propose that NPQ itself holdspotential as an easily acquired optical signal indicative of phytoplanktonphysiological state with respect to Fe limitation. We present data from a research voyage to the Subantarctic Zone south ofAustralia. Incubation experiments confirmed that resident phytoplankton wereFe-limited, as the maximum quantum yield of primary photochemistry, F v ∕ F m ,measured with a fast repetition rate fluorometer (FRRf), increasedsignificantly with Fe addition. The NPQ capacity of the phytoplanktonalso showed sensitivity to Fe addition, decreasing with increased Feavailability, confirming previous work. The fortuitous presence of a remnantwarm-core eddy in the vicinity of the study area allowed comparison offluorescence behaviour between two distinct water masses, with the colderwater showing significantly lower F v ∕ F m than the warmer eddy waters,suggesting a difference in Fe limitation status between ...